Evaluating the User Experience of Type 1 Diabetes Control Applications - Moreira, Francisco; Coutinho, Emanuel (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2023)
Type 1 diabetes is a chronic condition that affects millions of people around the world. For those, facing daily challenges is a reality, from constantly monitoring blood glucose levels to administering adequate doses of insulin. With the advances in E-Health technology and the improvement of ubiquitous applications and systems, new solutions are emerging to help people in their diabetes control, such as devices that send blood glucose levels via bluetooth to the control app, and subcutaneous sensors that are applied to the arm and monitor the blood glucose levels constantly. Despite the practicality that these systems present, their applications have scores below 3.5 stars on their respective platforms, showing dissatisfaction on part of its users. This article aims to evaluate the user experience of the apps G-Tech App and FreeStyle Libre. Both are ubiquitous applications for control of type 1 diabetes, although they have a different approach. For this, the extended MALTU evaluation was used and a bibliographical research was carried out. The evaluation consists of analyzing users' spontaneous comments on social systems, such as Play Store and App Store. The results revealed problems that hinder the user's interaction with the application, mainly regarding synchronization and functionalities.